2006
DOI: 10.1097/01.qai.0000243055.65698.51
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV Antibody Testing in the New York State Anonymous HIV Counseling and Testing Program

Abstract: Rapid testing presents a key opportunity to increase the number of people undergoing HIV testing and the proportion receiving their test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 5 publications
2
41
1
Order By: Relevance
“…We found that 65% of individuals who received a positive rapid test or a positive ELISA test that was validated by a confirma- tory test returned for the results, which was somewhat lower than the rates reported in studies that were conducted in community-based testing sites, which ranged from 75% to 89% (Antonio-Gaddy et al, 2006;CDC, 2007;Guenter et al, 2008). We also found that citizenship status, housing status, and health insurance status were independently associated with receiving a confirmatory HIV test and returning for the results.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…We found that 65% of individuals who received a positive rapid test or a positive ELISA test that was validated by a confirma- tory test returned for the results, which was somewhat lower than the rates reported in studies that were conducted in community-based testing sites, which ranged from 75% to 89% (Antonio-Gaddy et al, 2006;CDC, 2007;Guenter et al, 2008). We also found that citizenship status, housing status, and health insurance status were independently associated with receiving a confirmatory HIV test and returning for the results.…”
Section: Discussioncontrasting
confidence: 39%
“…Prior studies have reported that between 50% and 100% of individuals who receive a reactive rapid HIV test take a confirmatory HIV test (Antonio-Gaddy et al, 2006;Begley et al, 2008;Brown et al, 2007;CDC, 2007;Guenter et al, 2008;Kelen et al, 1999) and between 49% and 100% of the individuals who receive a confirmatory HIV test return for the results (Antonio-Gaddy et al, 2006;Begley et al, 2008;Bucher et al, 2007;CDC, 2007;Delaney et al, 2011;Freeman, Sattin, Miller, Dias, & Wilde, 2009;Guenter et al, 2008, Kassler et al, 1997Spielberg et al, 2005). To date, no studies have examined the predictors of returning for confirmatory HIV test results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other research suggests that the clients may also prefer rapid HIV testing to conventional HIV testing. 10,[19][20][21][22] Our findings highlight several issues that are important for CBOs to consider prior to implementing rapid HIV testing programs in community or outreach settings. CBOs need to plan for and ensure that staff members who will perform HIV counseling and rapid HIV testing receive appropriate training.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…11 However, the implementation of rapid testing in New York State in 2003 meant that 100% of those tested received their result and led to a 36% increase in testing over the previous year resulting in increased detection of previously undiagnosed HIV. 8 A further advantage of rapid HIV tests is that they are ideally suited to non-clinical or community settings, providing access to HIV testing to individuals who might not otherwise access clinical services for testing. Oral fluid sampling may confer added benefits to users over finger prick blood testing as it may be perceived as less invasive and is less painful.…”
mentioning
confidence: 99%